APPLICATION OF THE PROPORTIONAL TEST IN THE ARGUMENTATION OF JUDICIAL RESOLUTIONS IN THE FIELD OF CIVIL LAW - Moisés Pablo Mariscal Rivera (2019)
The legal system is not permanent, complete, consistent and clear; on the contrary, due to the globalization in technology and information, as well as to the profuse legislative production it has become complex and contradictory, originating internal and external antinomies, being that before this problematic the Civil Judge has chosen to make a specific application of the law. This research article is aimed at granting the Civil Judge the possibility of using the Proportionality Test, so that the argumentation of his decision is not based on the literal application of the law, but is carried out from the perspective of Fundamental Rights and Constitutional Principles involved in the specific case.